Evaluating the Determinants of Consumer Adoption of Autonomous Vehicles in Thailand—An Extended UTAUT Model - Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok; Kamales, Nayika; Dacko-Pikiewicz, Zdzislawa; Liszewski, Wiesław; Khalid, Bilal (Energies (Basel), 2023)
This study explores the effects of autonomous cars and how they may affect the design of transportation systems. The research investigated the determinants of consumer adoption of autonomous vehicles in Thailand. The research was driven by increasing environmental protection awareness and the need to conserve it through revolutionary technology. The study adopted the extended UTAUT model, where a quantitative method was adopted using primary data from 381 respondents. The results indicated that consumer adoption of autonomous vehicles in Thailand is influenced by performance expectancy, effort expectancy, facilitating conditions, environmental benefits, and purchase subsidy. The recommendations developed were that, to enhance the consumers’ intention to adopt autonomous vehicles, the concerned stakeholders should improve on aspects, such as the ability to improve job performance, increase productivity, ease of use, flexibility, clarity, and understanding, as well as improve social status. The government should also consider subsidizing autonomous vehicles as this would encourage consumption. A limitation of the study is the generalization of the findings as it is limited to Thailand.